Pengaruh Pengaruh ROA, ROE, dan EPS Terhadap Harga Saham Perusahaan Sektor Farmasi yang Terdaftar di BEI Tahun 2018-2022 - Nus Dencoco Samosir; Rosinta Pakpahan; Tasya Bernatha Hia; Wasima Agita Maharani; Rossy Pratiwy Sihombing (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Abstract The economy experienced a significant decline in growth in the movement of the Jakarta Composite Index (IHSG) in the capital market as a result of the Covid-19 pandemic, even dropping below the 4,000 level in March 2020. This study aims to analyse the effect Return on Assets (ROA), Return on Equity (ROE), and Earning per Share (EPS) on the stock prices of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). This study uses a comparative causal method (causal-comparative Research) by using secondary data. The population used in this study are pharmaceutical sector companies listed on the Indonesia Stock Exchange (IDX) in the range from 2018 to 2022. Sampling in this study was to use the purposive sampling. The statistical test method used to test the hypothesis in this study is the partial t test and simultaneous f test. Based on the results of the analysis, it can be concluded that the variables that affect stock prices are EPS, while the variables ROA and ROE do not significantly affect stock prices, but based on the results of the simultaneous f test it is obtained that ROA, ROE, EPS have a jointly significant effect on prices share.